Guidance for the preparation of neurological management guidelines by EFNS scientific task forces – revised recommendations 2012. Issue 3 (16th January 2013) - Leone, M. A.; Brainin, M.; Boon, P.; Pugliatti, M.; Keindl, M.; Bassetti, C. L.
Abstract : This paper is meant to provide guidance to anyone wishing to write a neurological guideline for diagnosis or treatment, and is directed at the Scientist Panels and task forces of the European Federation of Neurological Societies (EFNS). It substitutes the previous guidance paper from 2004. It contains several new aspects: the guidance is now based on a change of the grading system for evidence and for the resulting recommendations, and has adopted The Grading of Recommendations, Assessment, Development and Evaluation system (GRADE). The process of grading the quality of evidence and strength of recommendations can now be improved and made more transparent. The task forces embarking on the development of a guideline must now make clearer and more transparent choices about outcomes considered most relevant when searching the literature and evaluating their findings. Thus, the outcomes chosen will be more critical, more patient‐oriented and easier to translate into simple recommendations. This paper also provides updated practical recommendations for planning a guideline task force within the framework of the EFNS. Finally, this paper hopes to find the approval also by the relevant bodies of our future organization, the European Academy of Neurology.